The Effect of Using Interactive Virtual Laboratory on High School Students Critical Thinking Skills on Blood Circulation System Material - Nisa Rahmasari; Raharjo Raharjo (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
The role of the laboratory in education can improve skills, including scientific process skills such as analyzing, evaluating, and thinking. One of the thinking skills is high-level thinking involving complex judgment skills, such as critical thinking, but students' critical thinking skills in Indonesia need to be improved. One of the Biology materials that can be carried out in practice is the Human Circulatory System, including the blood group system and heart organ function concepts. It requires expensive tools and materials and avoids disease transmission, so an interactive virtual laboratory medium is needed, one of which is the Howard Hughes Medical Institute (HHMI). This study aimed to determine the effect of using the HHMI interactive virtual laboratory on the critical thinking skills of XI Senior High School students in the Human Circulatory System Material Heart Organ Subchapter. The research used the experimental method and quantitative research. The research design was a Post-Test-Only Control Design, providing a post-test for the experimental and control groups after treatment. The statistical analysis was non-parametric to test the Mann-Whitney U hypothesis with a significance level of 0.05 with SPSS 23. Based on the results of data analysis, it was found that the results of critical thinking skills had a significant difference based on the results of hypothesis testing, with a Sig value of 0.010 at a significant level of 5%. Based on these results, interactive virtual laboratories affect students' critical thinking skills.